Hybrid optical and acoustic resolution optoacoustic endoscopy - He, Hailong; Wissmeyer, Georg; Ovsepian, Saak V.; Buehler, Andreas; Ntziachristos, Vasilis (Optics Letters, 2016)
We propose the implementation of hybrid optical and acoustic resolution optoacoustic endoscopy. Laser light is transmitted to tissue by two types of illumination for achieving optical and acoustic resolution imaging. A 20 MHz ultrasound detector is used for recording optoacoustic signals. The endoscopy probe attains a 3.6 mm diameter and is fully encapsulated into a catheter system. We validate the imaging performance of the hybrid endoscope on phantoms and ex vivo, and discuss the necessity for the extended resolution and depth range of endoscopy achieved.
CRIS-Team Scopus Importer:2023-03-08